The moral imperative to prioritize mental health care in primary health care services: a bioethical analysis - Dithung, Reabetswe (My University, 2022)
Despite the emergence of bioethical and human rights protections, intergenerational injustices and violations in the mental health care context have exacerbated the vulnerability of mental health care users (MHCUs) and mentally ill patients. The relationship between mental health and socio-economic development largely coincides with the emergence of colonialism. South Africa’s historical period reveals an important correlation between mental health and socioeconomic development. Research has revealed that mental ill-health and poverty interact in a negative cycle. This relationship has had detrimental consequences on the right to access appropriate, available and quality mental health care. Given the historical propensity for using mental health as a tool of oppression, it is vital to interrogate and scrutinize mental health care laws, policies and practices in South Africa against the backdrop of its socio-cultural, socioeconomic and socio-political contexts. Indigenous healing practices formed part of African culture and healthcare prior to the arrival of western medicine. An individual’s capability to be healthy is limited when social, cultural, and economic injustices infringe upon a person’s dignity and their freedoms are left unaddressed. Mental health care, therefore, ought to be prioritized in primary health care (PHC) services to improve South Africa’s socio-economic development, on the basis of African thought, bioethics and human rights.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine (Bioethics & Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022